THE RELATION BETWEEN ELECTRIC AND REDOX POTENTIAL: EVIDENCE FROM LABORATORY AND FIELD MEASUREMENTS - Timm F.; Moller P. (My University, 2001)
In field and laboratory experiments the relationship of redox, electric, and total potential was studied. This was carried out by using different arrangements of Pt and Ag/AgCl electrodes. The total potential is obtained by placing a Pt and an Ag/AgCl electrode at considerable distance apart on the rock. The studies indicate that the total potential yields the sum of redox and electric potential. Deviations larger than a couple of mV are caused by extensive fluid-rock interactions. In the laboratory it is seen that the magnitude of the electric potential is generally not larger than the artificially produced difference of the redox potential. The former is most likely attributed to a diffusion or membrane potential. At field scale the electric potential is designated as self potential. Redox potential measurements in the field may supply information from remnants of pore fluid of the rock and thereby may be suitable to support the exploration of concealed metal deposits. Detectable are in particular the fast H+ ions which are released by electrochemical reactions and transported by electromigration, both of which are attributed to the presence of the so called geobattery.
Keywords: REDOX POTENTIAL; ELECTRIC POTENTIAL; SELF POTENTIAL; ELECTROCHEMICAL REACTION; ELECTROMIGRATION; CONCEALED ORE